Importance of ectopic thyroid tissue detected in the midline of the neck: single center experience - Oguz,Ayten (2016)
Objective Ectopic thyroid tissue (ETT) is a rare abnormality of the thyroid gland and the true prevalence and importance is not known. The aim of this study was to evaluate ultrasonography (US) guided fine needle aspiration biposy (FNAB) results, sonographic features, and frequency of ETT detected in the midline of the neck. Subjects and methods Five thousand five hundred and twenty outpatients who were referred to our thyroid clinic between September 2010 and April 2012 and underwent thyroid US, were retrospectively analyzed. Patients with ETT, detected in the midline of the neck in US were included in the study. Thyroid functions, sonographic features, and US guided FNAB results were evaluated. Results There were 81 (81.8%) female and 18 (18.2%) male patients with a mean age of 50.9 ± 11.7. The ETT in the midline was present in 1.79% (99/5,520) of the patients. In the majority of the patients, benign sonographic features (isoechoic, regular margin, type 1 vascularization) were detected. There were 92 (92.9%) patients with a previous history of thyroidectomy and all were histopathologically benign. In 7 (7.1%) patients, there was no history of thyroid operation. FNAB results of ETT were benign. Conclusion This study evaluated the importance of ETT detected incidentally in the midline of the neck. Especially in patients with a history of thyroidectomy, the thyroid masses in the midline of the neck can be found as incidental with imaging methods. Our results suggests that the incidence of malignancy in this group is much lower than orthotopic thyroid nodules and they are often benign.